Activating Mutations in ERBB2 and Their Impact on Diagnostics and Treatment - Herter-Sprie, Grit S.; Greulich, Heidi; Wong, Kwok-Kin (Frontiers in Oncology, 2013)
Despite the ongoing ‘war on cancer’, cancer remains one of the major causes of human morbidity and mortality. A new paradigm of targeted therapies holds the most promise for the future, making identification of tumor-specific therapeutic targets of prime importance. ERBB2, best known for its role in breast cancer tumorigenesis, can be targeted by two types of pharmacological manipulation: antibody therapy against the extracellular receptor domain and small molecule compounds against the intracellular tyrosine kinase domain. Aberrant activation of ERBB2 by gene amplification has been shown to participate in the pathophysiology of breast, ovarian, gastric, colorectal, lung, brain and head and neck tumors. However, the advent of next-generation sequencing technologies has enabled efficient identification of activating molecular alterations of ERBB2. In this review, we will focus on the functional role of these somatic mutations that cause ERBB2 receptor activation. We will additionally discuss the current preclinical and clinical therapeutic strategies for targeting mutationally activated ERBB2.